SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP MENGGUNAKAN METODE WEIGHTED PRODUCT - sindhu rakasiwi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Abstract The appearance of laptops of various kinds and sizes. Very good prices for domestic production and foreign production. Often people make purchases just because they are interested in the latest model or appearance and facilities without adjusting to their needs. This causes a discrepancy between the goods, functions and facilities available. Anugerah Ungaran Computer Store sells a variety of computers or laptops, but consumers in choosing a laptop that suits their needs. Resulting in the process of buying old items by consumers who want to buy a laptop directly. Using the weighted product method can produce a decision support system that can help consumers in choosing the laptop to be purchased. From the results of the validation test conducted by the expert the final prediction is 2.5, the system is declared valid. With a system that supports laptop decisions can be accessed by consumers and consumers can access themselves online.